Who is afraid of the Asset Quality Review? Potential losses and capital shortfalls in the European banking system - Thomas Bonczek; Clemens Fuest; Michael Schröder (Frankfurt School of Finance & Management, 2014)
[Introduction ...] The rest of this paper is set up as follows. In section 2 we provide a brief description of the ECB's comprehensive assessment of the European banking system. In section 3 we describe the data we are using and provide some descriptive statistics, particularly regarding the changes between the years 2012 and 2013. Section 4 includes the scenarios and the results of our analysis. In section 5 we discuss the findings and the policy conclusions emerging from the analysis.
Keywords: 330